Print Literacy Humiliation: Translanguaging and emotions with newcomer children - Brubacher, Katie (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
Emotions not only take us deeper in but also reveal larger political and historical structures that dominate how the Grades 4 to 6 newcomers with emerging print literacy in this study shape their literacy practices. Following a humanizing approach, I conducted three qualitative, critical case studies in Ontario urban schools. Data collection tools included in this article include plurilingual texts, focus group interviews and field notes. Through a thematic deductive analysis, themes emerged such as desire and written English, and print literacy humiliation. Moving away from historically oppressive, English-only structures in the classrooms, created more excitement and pride around writing and language.